Cysteine Proteinases and the Pathogenesis of Amebiasis - Que, Xuchu (American Society for Microbiology, 2000)
Amebiasis is a major cause of morbidity and mortality throughout the tropical world. Entamoeba histolytica is now recognized as a separate species from the morphologically identical E. dispar, which cannot invade. Cysteine proteinases are a key virulence factor of E. histolytica and play a role in intestinal invasion by degrading the extracellular matrix and circumventing the host immune response through cleavage of secretory immunoglobulin A (sIgA), IgG, and activation of complement. Cysteine proteinases are encoded by at least seven genes, several of which are found in E. histolytica but not E. dispar. A number of new animal models, including the formation of liver abscesses in SCID mice and intestinal infection in human intestinal xenografts, have proven useful to confirm the critical role of cysteine proteinases in invasion. Detailed structural analysis of cysteine proteinases should provide further insights into their biochemical function and may facilitate the design of specific inhibitors which could be used as potential chemotherapeutic agents in the future.